Decoy effect, anticipated regret, and preferences for work-family benefits - REB, Jochen (Institutional Knowledge at Singapore Management University, 2018)
Attracting talent is one of the key challenges for organizations, and offering attractive work-family benefits plays an increasingly important role in succeeding at this challenge. However, behavioural decision theory suggests that when choosing among job offers with different work-family benefits, individuals may fall prey to a decoy effect and this effect may be mediated through anticipated regret. This effect occurs when preferences are influenced by a normatively irrelevant decoy option that is clearly inferior to one of the other options in the choice set, but not the other (i.e., ‘asymmetrically dominated’). Across two studies, we investigated preferences for two important types of work–family benefits: flexible work arrangements (FWA) and dependent care support (DCS). We predicted and found a decoy effect: Preferences for jobs with these benefits were influenced by the presence of a normatively irrelevant decoy option. That is, preferences shifted towards either the FWA option or the DCS option depending on which option the decoy targeted (i.e., the option that asymmetrically dominated the decoy). The effects held over and above variables related to individuals’ work and family situations and values, including role centrality. Moreover, we found that anticipated regret mediated the effect of the decoy option on benefit preferences.